Realização de valores pessoais no ambiente organizacional e saída voluntária - Gonçalves, Daniela Borracha (2017)
It is essential that companies make investments in the retention and attraction of human capital. Avoiding the voluntary departure of employees, especially those with better skills and capabilities, and creating a favorable working environment for them to remain have become important goals for organizations. For this, it is necessary to understand what factors lead the individual to voluntarily leave. The main objective of this study is to analyze the contribution of perception of non-realization of personal values to the voluntary departure of the organization, through the following specific objectives: to identify the most important personal values of the participants and to identify if the perception of non- Organizational environment is considered in the process that led to the voluntary departure of the organization in which they acted. In order to meet these objectives, the voluntary exit constructs were presented, considered as the result of a process with several stages that culminates with the act of leaving the organization, and perception of realization of personal values in the organizational environment (RVP), defined as the Perception of accomplishment of personal motivational goals in the organizational environment in which people act when performing their daily activities. In order to broaden the approaches used to investigate personal values and PVR, in this study we used the qualitative approach, based on semi-structured interviews, with elements of the laddering method. The participants were eight professionals who had participated in the same trainee program early in their careers and had approximately 10 years of experience. From the categorical analysis of the transcripts it was possible to identify the most important first-order motivational types, Self-Direction and Stimulation, both goals related to Openness to Change, and Achievement (Self-Enhancement). In the voluntary decision-making process of participants in this study, different times for voluntary exit were identified. The perception of not realizing the most important personal values in the organizational environment in which they acted was a factor considered in this process, including the decision to exit to other areas of the organization.